Buying defence and security in Europe : the EU Defence and Security Procurement Directive in context - Trybus, Martin (Cambridge : Cambridge University Press, 2014)
Buying Defence and Security in Europe is the first critical evaluation of the EU Defence and Security Procurement Directive 2009/81/EC, which is now the basis for public and private entities buying armaments and sensitive goods and services in the EU. This instrument aims to ensure non-discrimination, competition and transparency in the security sectors. Part one provides a critical analysis of the economical, historical, political, military-strategic and legal contexts of the new EU Defence and Security Procurement Directive. Part two covers the main aspects of the Directive: its scope, procedures, security of supply and information, offsets and subcontracting, and finally its review and remedies system. This book is an essential overview of a legislative milestone in the field.
The political and economic context of the Defence Directive : buyers, sellers, and national security -- The legal base of the Defence Directive in EU internal market law : prohibitions, exemptions, and proportionality -- Defence derogations from the treaty : articles 346 and 347 TFEU -- The EU law and policy context beyond the Defence Directive : intra-community transfers, exports, standardisation, competition law, mergers, and state aids -- European armaments law and policy outside the EU internal market : EDA, OCCAR, letter of intent, and NATO -- Inside or outside the Defence Directive : limitation of scope -- Security through flexibility : the procurement procedures of the Defence Directive -- Security of supply and security of information : description in the specifications, contract conditions, qualification and award criteria -- Addressing the structure of the European Defence industries : substituting offsets with subcontracts? -- The'hidden remedies directive' : review and remedies in the Defence Directive.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: European Parliament; Defense contracts -- European Union countries